(untitled) (Annals of Medical Research, 2021)
Alport syndrome is a type IV collagen synthesis disorder characterized by hereditary progressive glomerular disease resulting from glomerular basement membrane injury, often accompanied by hearing loss and ocular defects. The most common form is X-linked Alport syndrome, which accounts for 80% of all cases. Although women mainly present with mild urinary symptoms, end-stage renal disease onsets at an early age in men. An 11-year-old girl was admitted to our hospital with mild bifissure oedema for the last 3 months. This study discusses the clinical, morphological and transmission electron microscopic findings of a rare case of Alport syndrome in the context of the wider literature.